Performing women/performing womanhood : theatre, politics, and dissent in North India - Bhatia, Nandi, 1963- (New Delhi : Oxford University Press, 2010)
This book examines diverse modes of dramatic representation and performance-myth, folklore, ritual, and history, including everyday conversation-used by women to intervene in and challenge the agenda of social movements, which conceptualized women's emancipation but imagined their role as being primarily at the core of family life.
Constructing the theatre actress -- Argumentative women in domestic spaces -- Independence, partition, and new theatrical imaginings -- From social reform to social protest -- The courtesan as 'virangana' in contemporary historical drama -- 'A window into an elegant and colourful, but almost forgotten world.'
Includes bibliographical references (pages 136-149) and index
Keywords: Women -- India, North -- Social conditions; Women in the theater -- India -- History -- 20th century